Supercontinuum Generation using Mode-Locked picoseconds Pulse Laser - S. W. Harun; M. R. A. Moghaddam; H. Ahmad (Jurnal Fisika dan Aplikasinya, 2011)
Supercontinuum (SC) generations in two nonlinear fibers are demonstrated using a passively mode-locked Erbium-doped fiber laser (EDFL). The EDFL is constructed using a semiconductor saturable absorber to generate 1.3 ps pulses with average power of 4.9 mW and repetition rate of 9.9 MHz at 1564 nm. The picosecond pulses are amplified by an Erbium-doped fiber amplifier to achieve an average output power of 13 dBm before it is launched into a 50m long photonic crystal fiber (PCF) and 100 m long highly nonlinear fiber (HNLF) for SC generation. Continuums starting from 1210 nm and 1370 nm for PCF and HNLF, respectively up to wavelength region of more than 1750 nm are achieved with average power of 10 dBm, which corresponds to 50% power conversion efficiency from pump to continuum.